ISLAMIC STUDIES DALAM PERSPEKTIF ILMU-ILMU HUMANIORA - Ichwansyah Tampubolon (Universitas Muhammadiyah Tapanuli Selatan, 2019)
The discipline of humanities sciences pay attention to dimensions of normative and historicalIslam by using monodisciplinary perspective.Themonodisciplinary perspective can usually be used to explore, describe, and explain each of the normative aspects of Islamic doctrines and that of Islamic historical realities or the relation of that two aspects. On the one hand, monodisciplinary perspective of humanities sciences due to make a great contribution to developingactivities of Islamic Studies inthe field of units analysis, methodologiesof research and models of interpretationofnormative and historical Islam specifically and deeply. And the otherhand, there are some weaknesses of monodisciplinary perspective of humanities sciences, because of it’s restricted views of cultural aspectsan sich, hence, it’s not comprehensively and integrally able to explore, describe, explain and to make solutionstocomplexity of the problems of human being.Key word: Islamic Studies, Monodisciplinary, Perspective, Social Sciencies, and Humanities